203k views
5 votes
Help please out of school due to medical issues. Thank you.

Help please out of school due to medical issues. Thank you.-example-1

1 Answer

6 votes

Question:

Solution:

Consider the following two functions:


f(x)=2x+8

and


g(x)=x^2+2x-8

Now, consider the following definition:


(f-g)(x)=f(x)-g(x)

thus, we get:


\begin{gathered} (f-g)(x)=f(x)-g(x) \\ =\text{ (2x+8)-(}x^2+2x-8\text{)} \end{gathered}

this is equivalent to:


=\text{ 2x+8-}x^2-2x+8

this is equivalent to:


=-x^2+16

So that, we can conclude that the correct answer is:


(f-g)(x)=-x^2+16

Help please out of school due to medical issues. Thank you.-example-1
User Madhan Raj
by
5.2k points